Implementation and Operational Research: The Navigation Program. (1st February 2016) - Wohl, Amy Rock; Dierst-Davies, Rhodri; Victoroff, Alla; James, Saloniki; Bendetson, Jesse; Bailey, Jeff; Daar, Eric; Spencer, LaShonda; Kulkarni, Sonali; Pérez, Mario J.
Abstract : Abstract: The Navigation Program is a health department-community agency collaboration to reengage lost HIV clinic patients in Los Angeles County using best practices from disease investigator services locator activities and the Antiretroviral Treatment Access Study (ARTAS), a CDC-recommended intervention. Clinic databases were reviewed to identify HIV patients who: (1) had no HIV care visits in 6–12 months and last viral load was greater than 200 copies per milliliter; (2) had no HIV care visits in >12 months; (3) were newly diagnosed and never in care; or (4) were recently released from jail/prison/other institution with no regular HIV medical provider. Patients were contacted by trained Navigators using locator information from clinic medical records, HIV/sexually transmitted disease surveillance, and people-finder databases and offered enrollment in a modified ARTAS intervention. Among the 1139 lost clinic patients identified, 36% were in care elsewhere, 29% could not be located, 8% returned to the clinic independently, 4% declined enrollment, and 7% (n = 78) were located and enrolled in the intervention. Participants received an average of 4.5 Navigator sessions over 11.6 hours. Among reengaged patients, 68% linked within 3 months, 85% linked within 6 months, and 94% linked within 12 months, and 82% of linked patients were retained in care 12 months after study enrollment. The percentage of linked patients virally suppressed was compared at time of linkage by the Navigators (52%) with a second viral load measure after linkage to care (63%) (χ 2 = 11.8; P = 0.01). The combined disease investigator services/ARTAS model of reengagement was effective for locating and reengaging lost HIV clinic patients. Access to HIV surveillance data is critical for the efficient identification of persons truly in need of reengagement.